Extension Design on the Production of Vegetable Pesticide from Belt Leaves in Controlling Aphids on Red Chilli in Kayukebek Village Pasuruan - Jumadin, Jumadin; Gunawan, Gunawan; Navitasari , Lisa (CV. Komunitas Dunia Peternakan, 2024)
Kayukebek Village is one of the villages that has the potential for agricultural development in horticultural crop commodities, especially red chilies due to high market demand and quite good agricultural productivity, namely around 8.42 tons/Ha. However, the obstacle often faced by farmers is the attack of aphids on red chili plants, resulting in a decrease in production. The aim of this research is to design an extension design and analyze the increase in farmers' knowledge, attitudes and skills regarding the use of botanical pesticides in controlling aphids. The research was conducted from January to May 2024. The research method used was the Level III action research method with the stages followed, namely planning, action, observation and reflection. The results of observation and reflection show that extension is able to increase farmers' knowledge by 44%, from the pre-test value of 47%, it increases to 91% in the post-test value with a percentage of extension effectiveness of 82% and is in the effective category. Meanwhile, in the attitude aspect, the percentage is 87%, and in the skills aspect it is 93%, which can be categorized as a very high score. These results show that the extension design implemented has proven to be effective in changing farmers' behavior both in increasing knowledge and determining attitudes as well as developing farmers' skills in making vegetable pesticides to control aphids on red chili plants.